Momentary Assessment of Adults’ Physical Activity and Sedentary Behavior: Feasibility and Validity - Dunton, Genevieve F.; Liao, Yue; Kawabata, Keito; Intille, Stephen (Frontiers in Psychology, 2012)
Introduction: Mobile phones are ubiquitous and easy to use, and thus have the capacity to collect real-time data from large numbers of people. Research tested the feasibility and validity of an Ecological Momentary Assessment (EMA) self-report protocol using electronic surveys on mobile phones to assess adults’ physical activity and sedentary behaviors. Methods: Adults (N = 110) (73% female, 30% Hispanic, 62% overweight/obese) completed a four-day signal-contingent EMA protocol (Sat. - Tues.) with eight surveys randomly spaced throughout each day. EMA items assessed current activity (e.g., Watching TV/Movies, Reading/Computer, Physical Activity/Exercise). EMA responses were time-matched to minutes of moderate-to-vigorous physical activity (MVPA) and sedentary activity (SA) measured by accelerometer immediately before and after each EMA prompt. Results: Unanswered EMA prompts had greater MVPA (±15 min.) than answered EMA prompts (p = .029) for under/normal weight participants, indicating that activity level might influence the likelihood of responding. The 15-min. intervals before vs. after the EMA-reported physical activity (n = 296 occasions) did not differ in MVPA (p > .05), suggesting that prompting did not disrupt physical activity. SA decreased after EMA-reported sedentary behavior (n = 904 occasions) (p < .05) for overweight and obese participants. As compared with other activities, EMA-reported physical activity and sedentary behavior had significantly greater MVPA and SA, respectively, in the ±15 minutes of the EMA prompt (p’s < .001), providing evidence for criterion validity. Conclusions: Findings generally support the acceptability and validity of a four-day signal contingent EMA protocol using mobile phones to measure physical activity and sedentary behavior in adults. However, some MVPA may be missed among underweight and normal weight individuals, and EMA may disrupt sedentary behavior among overweight/obese individuals.